PERBANDINGAN KUAT TEKAN PAVING BLOCK RAMAH LINGKUNGAN BERBASIS LIMBAH BOTOL PLASTIK KEMASAN AIR MINERAL DENGAN LIMBAH CANGKANG KERANG DAN LIMBAH BOTOL KACA SEBAGAI BAHAN SUBSTITUSI TERHADAP SEMEN - Indah Handayasari; Gita Puspa Artiani (Construction and Material Journal, 2019)
Among various kinds of alternative building material products used as cover or hardening of soil surface, Paving blocks are products that are in great demand by consumers. As a covering material and ground surface hardening, Paving blocks are widely used for various purposes, ranging from hardening and beautifying road sidewalks, road hardening, hardening of parking areas, and can even be used in special areas such as container ports and airports. This is because Paving blocks have advantages from other products in terms of shape, size, color and style. In addition, Paving blocks can be combined with other cover materials. Considering the use of Paving blocks that are quite extensive, it is necessary to have alternative substitute materials that can reduce the use of natural materials due to increased physical infrastructure development but are environmentally friendly. One of the eco-friendly Paving block alternatives is by utilizing plastic bottle waste packaging as mineral water as sand substitution material as well as green seashell waste and glass bottle waste as cement substitution material in making Paving blocks. In this study samples were made by comparing the composition of plastic bottle waste packaging of mineral water, seashell waste and glass bottle waste with 0%, 5%, 10%, 15% and 20% substitution treatment of the dry weight of Paving blocks. The test results showed that the optimum mixture variation was found in a mixture with a variation of 10% of plastic bottle waste packaging of mineral water + 10% of seashell waste with a compressive strength of 12.8 MPa and a percentage of water absorption at 28 days of 2.63%. Where the results of the variations in Paving blocks are categorized into quality C which can be used for pedestrians.Keywords : Paving Blocks, Waste, Compressive Strength.